Contextual Tafsir and Digital Islam in Southeast Asia: A Narrative Review - Saefulloh, Ahmad (Yayasan Sinergi Kawula Muda, 2024)
This narrative review explores the development of contemporary Qur'anic exegesis (tafsir) in Southeast Asia, a region marked by religious diversity and dynamic socio-political landscapes. The study aims to investigate how interpretative frameworks have evolved to address modern societal challenges while remaining grounded in classical Islamic traditions. Using a structured literature search across academic databases including Scopus and Google Scholar, the review analyzes scholarly contributions employing maqasid-based, thematic, pedagogical, and contextual methods. Criteria for inclusion prioritized peer-reviewed publications in English, Indonesian, and Malay from 2000 onwards. The findings reveal that contemporary tafsir in Southeast Asia is characterized by methodological plurality, the integration of digital technology, gender-inclusive interpretation, and responsiveness to local contexts. Maqasid-oriented tafsir emerges as a pivotal approach, enabling ethical and socially relevant interpretations of the Qur’an. The use of platforms like YouTube has expanded access to tafsir, while female scholars contribute significantly to more inclusive and egalitarian interpretations. Political structures and educational systems influence both the dissemination and institutionalization of tafsir. However, challenges remain, including rigid curricula, limited funding, and ideological control by state religious institutions. This review underscores the necessity for innovation, interdisciplinary engagement, and institutional support in sustaining a relevant and dynamic tafsir tradition. Southeast Asia offers valuable insights and models that can inform global tafsir discourse, particularly in pluralistic societies. Future research should explore emerging intersections with digital ethics, interfaith dialogue, and sustainable development.